Correlation between sagittal and inclined angles of cervical facet joints and cervical disc herniation: a radiological observational study - Weng, Rui; Liu, Hao; Lin, Dongxin; Guo, Haiwei; Mo, Ling; Liu, Hongjiang; Zhu, Genfu; Li, Yikai; Liu, Caijun; Huang, Xuecheng; Yao, Zhensong (Frontiers in Surgery, 2026)
BackgroundPrevious studies have found that asymmetry of cervical facet joints is associated with cervical disc herniation. However, the effect of facet joint angle on disc herniation is inconclusive. Further identification of the pathological anatomic features of cervical disc herniation is helpful for the prevention and treatment of the disease.ObjectiveTo explore the relationship between sagittal angle or inclined angle of cervical facet joint and CDH.MethodsAmong patients who visited the First Affiliated Hospital and the Third Affiliated Hospital of Guangzhou University of Chinese Medicine from June 2015 to December 2022, 271 patients with single-segment CDH (79 in C4/5 segment, 122 in C5/6 segment, and 70 in C6/7 segment) were screened for inclusion in the CDH group. At the same time, 132 age- and gender-matched healthy subjects were randomly enrolled as a control group. Data on the bilateral sagittal angles and inclined angles of cervical facet joints were collected from both groups. Intergroup comparisons were performed after Bonferroni correction and adjustment for confounding factors.ResultsThere were no significant differences in gender, age, or BMI between the two groups. However, the C2–7 Cobb angle was significantly smaller and the intervertebral disc height at the corresponding affected segments was significantly lower in the CDH group than in the control group (P < 0.05). Regarding the sagittal angle of facet joints: before correction, the bilateral differences and asymmetry rates of sagittal angles at all segments were significantly higher in the CDH group than in the control group (P < 0.05); after Bonferroni correction, only the difference at the C4/5 segment remained significant (P < 0.05). The average sagittal angle at the C5/6 segment was significantly higher in the CDH group than in the control group before correction (P < 0.05), but this difference disappeared after adjusting for confounding factors. Regarding the inclined angle of facet joints: before correction, the bilateral differences and asymmetry rates of inclined angles at all segments were significantly higher in the CDH group than in the control group (P < 0.05), but no significant differences were observed after correction. The average inclined angles at the C5/6 and C6/7 segments were significantly lower in the CDH group (P < 0.05), and these differences persisted after adjusting for confounding factors (P < 0.05).ConclusionSagittal angle asymmetry of facet joints at the C4/5 segment is associated with lower cervical disc herniation. A significant reduction in the average inclined angle (tendency to be horizontal) of the facet joints at the corresponding segments in patients with single-segment CDH at C5/6 and C6/7 is an important pathophysiological and anatomical characteristic of the disease. Additionally, the intergroup difference in the average sagittal angle may be influenced by the degree of cervical lordosis and intervertebral disc height.